2004
DOI: 10.1111/j.0906-6705.2004.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hsp90 protein expression in malignant melanomas and melanoma metastases

Abstract: The heat-shock protein Hsp90 has been shown to be essential for the functional integrity of the telomerase complex. The telomerase activity is enhanced in melanoma and stabilizes the chromosomal integrity in proliferating cells. Furthermore, overexpression of Hsp90 induces silencing of point mutations in transcription factors which, otherwise, would result in a loss-of-function phenotype. In melanocytic lesions there is a higher risk of mutations caused by the enhanced proliferation in melanocytic cells. By an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 29 publications
8
116
0
1
Order By: Relevance
“…However, because of lack of adequate mono-specific anti-Hsp90a and Hsp90b antibodies for FACS and IF, we are unable to state whether Hsp90a, in addition to Hsp90b, is also expressed at the SH-SY5Y cell surface. Cell surface Hsp90 (a/b) expression was also detected in pcDNA and TrkAIII transfectants, adding SH-SY5Y cells to other tumour and normal cell types that express cell surface Hsp90 (a/b) (Becker et al, 2004;Sidera et al, 2004Sidera et al, , 2008 and TrkAI to other cell surface receptors that depend on interaction with Hsp90 for stability (Vega and De Maio, 2003;Peng et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…However, because of lack of adequate mono-specific anti-Hsp90a and Hsp90b antibodies for FACS and IF, we are unable to state whether Hsp90a, in addition to Hsp90b, is also expressed at the SH-SY5Y cell surface. Cell surface Hsp90 (a/b) expression was also detected in pcDNA and TrkAIII transfectants, adding SH-SY5Y cells to other tumour and normal cell types that express cell surface Hsp90 (a/b) (Becker et al, 2004;Sidera et al, 2004Sidera et al, , 2008 and TrkAI to other cell surface receptors that depend on interaction with Hsp90 for stability (Vega and De Maio, 2003;Peng et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Our combined data showing association of cell surface HSP90 with migration processes in the developing nervous system attribute a novel biological role to this molecule. Moreover and taking into consideration very recent findings demonstrating expression of HSP90 on the surface of malignant melanoma tumor cells (52), it is tempting to speculate that this protein may be involved in tumor cell invasion processes during cancer metastasis. Indeed, while this manuscript was under review, Eustace et al (53) showed that HSP90␣ is localized on the surface of tumor cells and plays an important role in the metastatic process.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing analysis showed that the 52 clones represented 30 distinct antigens (Table 1). Of these 30 antigens, one is the CT antigen CAGE protein, and the other 13 antigens, which had previously been reported to be involved in tumorigenesis or suspected to be involved in tumour progression, including CDC37 (Stepanova et al, 2000), MIF (Li et al, 2004), galectin 4 (Huflejt and Leffler, 2004), galectin 8 (Bidon-Wagner and Le Pennec, 2004), PINCH (WangRodriguez et al, 2002), SPRY2 (Lee et al, 2004a), HSPCA (Becker et al, 2004;Huang et al, 2004b), transgelin 2 (Shields et al, 2002), HDAC2 , H factor (Junnikkala et al, 2000), AAT (Huang et al, 2004a), B factor (Perou et al, 1999), PIBF (Lachmann et al, 2004). Three other antigens (SR140 protein, SFRS2IP, RNPC2) may be involved in the regulation of alternative mRNA splicing, PSMA7 is related to hepatitis B and hepatitis C viral replication (Zhang et al, 2000;Kruger et al, 2001), and the remaining 12 antigens have no known association with cancer or hepatitis B or hepatitis C.…”
Section: Serex Defined Hcc-associated Antigensmentioning
confidence: 99%